Loģistikas analīze Eiropā: preču un pasažieru transporta nozarē Latvijas un Rumānijas piemērs - Badescu, Bogdan (Latvijas Universitāte, 2012)
The writer’s aim in this paper was to achieve a comparison between the present freight and passengers transport sector situation in Latvia and Romania. The researched information is presented as follows: firstly an analysis of transports in the European Union and then it is being detailed for both countries. The comparison ends with a table that summarizes the transport infrastructure in Latvia and Romania. Finally the writer chose to end the thesis with a case study on Riga International Airport.

he writer’s aim in this paper was to achieve a comparison between the present freight and passengers transport sector situation in Latvia and Romania. The researched information is presented as follows: firstly an analysis of transports in the European Union and then it is being detailed for both countries. The comparison ends with a table that summarizes the transport infrastructure in Latvia and Romania. Finally the writer chose to end the thesis with a case study on Riga International Airport.
Analysis of logistics in Europe:goods and passengers transport sector:case studies on Latvia and Romania
Keywords: Vadībzinātne